The Woman in Black: A Ghost Play - Porter, Gerry (2006)
Colour Petrina Bromley (director), with Aiden Flynn and Steve O'Connel. Sean Panting (sound design), Victor Tilley (light design), Pat Dempsey (effects operator) Resource Centre for the Arts (RCA)